Les affects et leur destin dans l’intervention - Jean-Yves Bonnefond; Yves Clot (Activités)
This paper examines the relationship between affectivity and activity during psychology interventions at work, particularly in terms of clinical activity. Different from emotion, affect is defined as a conflict within the activity, as a balance of power between what is expected and unexpected in the activity, the unpredictable future of which oscillates between two orientations, either more active or more passive. Based on an example from an intervention in the automotive industry, we show that the intervention causes movements in affectivity. During these movements, activity and passivity can be reversed, and one might eventually mutate into the other. Indeed, the dialogic clinical setting can be the source of a potential development of the affect, leading to an active orientation towards one condition: when the affect is the subject of repetition in another context, where repetition is not only permissible but specifically solicited by the intervention. In causing the affective movement, the intervention might regenerate it by "reloading" it with its own dialogical